(untitled) (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
The long-debated philosophical dilemmas such as ethics, consciousness, and free-will have become of considerable interest among the philosophers and scientists alike who work on artificial intelligence (AI). This study investigates how the Tiantai Buddhist concept of Buddha-nature can be incorporated into the ethics pertaining to "artificial animals" or bots, as "ethically charged machines." The major research problem addressed here is whether the thoughts of Tiantai Buddhist School on Buddha-nature can contribute to the improvement of AI-based technologies. This analysis uses certain philosophical developments in the school of New Materialism that rethinks the nature of matter, agency, and subjectivity by transcending old-fashioned dualisms for instance mind/body, human/nonhuman, and subject/object while emphasizing on the active, dynamic qualities of matter and the interconnectedness of all entities; blurring demarcations between human and nonhuman. The ideas of Jingxi Zhanran (711–782) from the Tiantai school, which assert that Buddha-nature exists not only in sentient beings but also in insentient things, will form a major premise of this argument. The study has used comparative analysis and hermeneutics as the research methodologies with academic interpretation and comparative analysis. The objective of the study is exploring the Tiantai concept of Buddha-nature in AI Ethics connecting with philosophical discourse found in the school of New Materialism. In conclusion, compassion and wisdom towards insentient beings that was neglected by the Western paradigms of ethics will throw a new light on AI ethics.